The Effect of the Implementation of the Family Hope Program (PKH) Policy on the Welfare of the Community in Cangkoak Village - Rahmat, Aurelia Febriyanti; Nursahidin, Nursahidin (Asian Journal of Social and Humanities, 2026)
The government launched the Family Hope Program as an effort to alleviate poverty among the poor. However, there are still several problems in its implementation, such as inaccurate and untargeted recipient data, as well as the large number of PKH recipients who are dependent on assistance. This study was conducted to examine the impact of the PKH policy implementation on the welfare of the Cangkoak Village community. The method used was a quantitative method through a causal association design. By distributing questionnaires to gather data, the study found a clear link between the PKH policy and increased community welfare. The statistical significance of this relationship is backed by a partial T-test; the calculated t-value (5.779) proved to be higher than the t-table value (1.99394) at the 5% alpha level. The conclusion of this study proves that PKH has an impact on community welfare in alleviating poverty by 32%. Therefore, this program must be improved by refining the data collection system for recipients to ensure it is on target, as well as the role of PKH assistants in encouraging the community not to become dependent on assistance.